NILAI-NILAI MOTIVASI PADA NOVEL “JENDERAL KAMBING” KARYA KHRISNA PABICHARA: TINJAUAN PSIKOLOGI SASTRA - Rizal Affandi; Wafiqotul Jamilah; Wildatur Rohimah; Abd. Aziz; Alfiyatul Hasanah (STKIP Subang, 2025)
This study aims to uncover the motivational values ​​in Khrisna Pabichara's novel Jenderal Kambing (Goat General) through a literary psychology approach with Sigmund Freud's psychoanalytic theory. The main focus of this study is how the main character, Ibrahim, generates motivation in facing various social pressures and inner conflicts. Data are analyzed based on the interaction between the id, ego, and superego elements within the character, as well as the forms of intrinsic and extrinsic motivation that influence his actions. The results of the analysis show that Ibrahim is a character who is able to manage inner pressure through healthy self-defense mechanisms, and has a strong motivation to achieve his life goals. This novel contains not only social values, but also psychological values ​​that reflect the process of identity formation and the strength of motivation in facing life's obstacles. This study is expected to provide a deeper understanding of the relationship between literature and psychology through characters in fictional works.